If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 7) + -4x = 12 Reorder the terms: 3(7 + x) + -4x = 12 (7 * 3 + x * 3) + -4x = 12 (21 + 3x) + -4x = 12 Combine like terms: 3x + -4x = -1x 21 + -1x = 12 Solving 21 + -1x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -1x = 12 + -21 Combine like terms: 21 + -21 = 0 0 + -1x = 12 + -21 -1x = 12 + -21 Combine like terms: 12 + -21 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9
| -2(x+7)=6x-38 | | 6.2/0.05 | | (2/-5)(8)(-9/3) | | 5[1/2-x]=5/4 | | 9=0.2x*0.2x*0.6x | | 9=0.2x*0.2x*0.06x | | 8h-4h+2=78 | | 1-7x=7x-1 | | 7x+2=12.5 | | X^2+X-110+2(4)=8 | | 16/2=n | | 2(9x+5)=190 | | x^2-15x-44=7x+4 | | x^2+x-38=9x-5 | | 5x+2=x+3.6 | | x^2+11x+31=1 | | 5x=8y+1 | | -7x-1.6=-5-1.2 | | 8m-0=16 | | 4(6x-9)=180 | | -7.4-2.4=-6x-2.9 | | U=5(2W-4W^3+5W^2) | | 6x+5=2x+65 | | 4/7*135 | | 3/64*4 | | 12x-228=3x-12 | | 9y-9=1 | | X^2+16-58=0 | | 1.3=26p | | 6x^2-5x+4h=0 | | 2(-3/2)-1 | | x^14-81=0 |